Exploring the interaction between learning styles and mathematics anxiety among secondary school students: A correlational study in southern Malaysia - Nur Aini Khoo binti Ahmad Fuad Khoo; Nurdiana Yasmin Jamaluddin; Sharifah Osman; Achmad Buchori (Journal of Technology and Science Education)
Mathematics is a subject that is extensively used in real-life situations, but it has been found to be a difficult subject to master. Accordingly, mathematics anxiety has been found to be highly prevalent in students’ lives, whereby learning styles have been underlined as one of the factors that may impact attainment of mathematics skills. This study aims to determine the relationship between learning styles and mathematics anxiety. The correlational study was conducted by using questionnaire adapted from Dunn and Dunn Model and Mathematics Anxiety Scale; involving 389 secondary school students located in the southern region of Malaysia. The study's findings revealed a positive correlation and distinguished between learning styles and mathematics anxiety. It shows that learning styles have an impact on mathematics anxiety. Hence, this study helps the students to embrace and improve their learning styles to minimize the level of anxiety towards mathematics, while the teachers may find it useful in guiding the students to control their mathematics anxiety.